2008
DOI: 10.1007/s10490-008-9095-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of personal and cultural factors on knowledge sharing in China

Abstract: Knowledge sharing, Guanxi orientation, Face saving, Face gaining, Theory of reasoned action, Social exchange theory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
211
3
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(237 citation statements)
references
References 39 publications
10
211
3
13
Order By: Relevance
“…Social exchange theory evaluates the cost and the perceived benefit before engaging in exchange behavior (Huang, Davison, & Gu, 2008;L. F. Liao, 2008).…”
Section: Reciprocal Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social exchange theory evaluates the cost and the perceived benefit before engaging in exchange behavior (Huang, Davison, & Gu, 2008;L. F. Liao, 2008).…”
Section: Reciprocal Relationshipsmentioning
confidence: 99%
“…If the cost is higher than the benefit, one would not participate in the action. Social exchange theory involves several social elements, such as social relationship, loyalty and commitment, and these are not being identified in the economic benefit (Huang et al, 2008;L. F. Liao, 2008).…”
Section: Reciprocal Relationshipsmentioning
confidence: 99%
“…Subjective Norm refers to a person's perception of normative beliefs (e.g., perceived pressures and motivation to pursue) and how most people who are important to him/her think he/she should or should not perform the behavior in question (Fishbein & Ajzen, 1975, p. 302;Huang, Davison, & Gu, 2008). According to TRA, a person's performance of a specified behavior is determined by his or her Behavioral Intention (BI) to perform the behavior, and BI is jointly determined by the person's Attitude towards using and Subjective Norm concerning the behavior in question.…”
Section: Subjective Norms (Sn)mentioning
confidence: 99%
“…Participants feel that they lose face if they share low-quality knowledge in networks. Losing face cost is a sociological perception of feeling embarrassment and disrespect in society (Huang et al 2008). This result is consistent with Ardichvili et al (2003) who found that users of online knowledge sharing communities are concerned about their own face during active participation.…”
Section: Perceived Costsmentioning
confidence: 99%